Pengaruh Profitabilitas, Intellectual Capital, dan Risiko Kredit terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Zazuli, Zena Muklis; Gusni, Gusni (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of profitability, intellectual capital, and credit risk on firm value, with institutional ownership as a moderating variable in Indonesian banking companies. Using panel data from 22 banks listed on the Indonesia Stock Exchange during 2020–2024, the study applies moderated regression analysis (MRA). The results show that profitability and intellectual capital positively affect firm value, while credit risk negatively affects firm value. Institutional ownership strengthens the effect of profitability, weakens the effect of intellectual capital, and does not moderate credit risk. These findings imply that balancing financial performance, intangible assets, and governance mechanisms is essential to enhance sustainable firm value.